Pengendalian Pasokan Produk Plumbing di Megah Grahaa Dengan SCM Method Berbasis Web - Bulan Rahmadani; Fauriatun Helmiah; Febby Madona Yuma (LPPM Universitas Bina Sarana Informatika, 2026)
Supply control in the distribution of plumbing products is vulnerable to fluctuations in demand and supplier delays. Based on observations at Megah Grahaa, supplier delivery delays of 2–4 days were found during periods of high demand, stock data discrepancies of around ±8% per month, and around 15% of slow-moving products stored for more than 60 days. These conditions indicate the need for a more integrated supply chain management system. This study aims to design and implement a web-based Electronic Supply Chain Management (E-SCM) system to improve the effectiveness of supply control. The system was developed using the Waterfall model, which includes needs analysis, system design using UML, implementation with PHP and MySQL, and testing using black-box testing. The results of the study show an increase in operational performance after the system implementation, where stock data discrepancies decreased from ±8% to less than 3% and the time to generate inventory reports was reduced from around 30 minutes to ±10 minutes. The system also enables real-time stock monitoring, thereby improving coordination between warehouses, suppliers, and management. These findings indicate that the implementation of E-SCM can improve inventory accuracy and supply control efficiency in building material distribution.